Elastin-Based Materials: Promising Candidates for Cardiac Tissue Regeneration - Gonzalez de Torre, Israel; Alonso, Matilde; Rodriguez-Cabello, Jose-Carlos (Frontiers in Bioengineering and Biotechnology, 2020)
Stroke and cardiovascular episodes are still some of the most common diseases worldwide, causing millions of deaths and costing billions of Euros to healthcare systems. The use of new biomaterials with enhanced biological and physical properties has opened the door to new approaches in cardiovascular applications. Elastin-based materials are biomaterials with some of the most promising properties. Indeed, these biomaterials have started to yield good results in cardiovascular and angiogenesis applications. In this review, we explore the latest trends in elastin-derived materials for cardiac regeneration and the different possibilities that are being explored by researchers to regenerate an infarcted muscle and restore its normal function. Elastin-based materials can be processed in different manners to create injectable systems or hydrogel scaffolds that can be applied by simple injection or as patches to cover the damaged area and regenerate it. Such materials have been applied to directly regenerate the damaged cardiac muscle and to create complex structures such as heart valves or new bio-stents that could help to restore the normal function of the heart or to minimize damage after a stroke. We will discuss the possibilities that elastin-based materials offer in cardiac tissue engineering, either alone or in combination with other biomaterials, in order to illustrate the wide range of options that are being explored. Moreover, although tremendous advances have been achieved with such elastin-based materials, there is still room for new approaches that could trigger advances in cardiac tissue regeneration